2013
DOI: 10.1094/pdis-06-12-0518-re
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fungicide Application on the Management of Avocado Branch Canker (Formerly Dothiorella Canker) in California

Abstract: Twizeyimana, M., McDonald, V., Mayorquin, J. S., Wang, D. H., Na, F., Akgül, D. S., and Eskalen, A. 2013. Effect of fungicide application on the management of avocado branch canker (formerly Dothiorella canker) in California. Plant Dis. 97:897-902.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While the least (%) success of avocado grafted seedlings on all cultivars in the two seasons were observed on Star copper and Bio Zeid. Twizeyimana et al (2013) found in vitro test that azoxystrobin, fludioxonil, metconazole, and pyraclostrobin inhibited the mycelial growth of Neofusicoccum america, N. luteum, N. parvum, and Phomopsis sp. which are associated with branch cankers of avocado trees (Persea americana) in California.…”
Section: Discussionmentioning
confidence: 97%
“…While the least (%) success of avocado grafted seedlings on all cultivars in the two seasons were observed on Star copper and Bio Zeid. Twizeyimana et al (2013) found in vitro test that azoxystrobin, fludioxonil, metconazole, and pyraclostrobin inhibited the mycelial growth of Neofusicoccum america, N. luteum, N. parvum, and Phomopsis sp. which are associated with branch cankers of avocado trees (Persea americana) in California.…”
Section: Discussionmentioning
confidence: 97%
“…In 1996, the manufacturer created metalaxyl-M (mefenoxam), a more active isomer of the fungicide, which is similarly applied (Olson and Benson 2013). Unlike metalaxyl and mefenoxam, which are xylem-mobile fungicides, phosphonate fungicides can move in both the xylem and phloem tissues (Cohen and Coffey 1986;Landschoot and Cook 2005;Twizeyimana et al 2013). The most effective and perhaps well-known phosphonate fungicide is fosetyl-Al, which was also developed in 1977.…”
Section: Fungicides For Oomycete Pathogen Managementmentioning
confidence: 99%
“…Symptoms of dieback are characterized by necrosis and death of twigs and branch-es in the tree canopy, with symptomatic plants exhibiting dry branches, external necrosis in twigs, and wilting leaves and inflorescences [ 3 , 4 , 5 , 6 , 7 ]. Cankers associated with Botryosphaeriaceae species (formerly Dothiorella canker ) can occur on branches and trunks, where infections are initiated by spores entering through fresh wounds resulting from pruning, mechanical injury, sunburn or frost damage [ 8 ]. Cankers on avocado may exudate reddish-brown sap that turns to a whitish-yellowish powder when dry [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cankers associated with Botryosphaeriaceae species (formerly Dothiorella canker ) can occur on branches and trunks, where infections are initiated by spores entering through fresh wounds resulting from pruning, mechanical injury, sunburn or frost damage [ 8 ]. Cankers on avocado may exudate reddish-brown sap that turns to a whitish-yellowish powder when dry [ 8 , 9 , 10 , 11 ]. The bark appears darkened and friable and can be easily removed in old cankers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation